2022
DOI: 10.3390/en15166027
|View full text |Cite
|
Sign up to set email alerts
|

State Characterization of Lithium-Ion Battery Based on Ultrasonic Guided Wave Scanning

Abstract: Accurate state characterization of batteries is conducive to ensuring the safety, reliability, and efficiency of their work. In recent years, ultrasonic non-destructive testing technology has been gradually applied to battery state estimation. In this paper, research on the state characterization of lithium-ion batteries based on ultrasonic guided wave (UGW) scanning is carried out. The laser Doppler vibrometer (LDV) and the X-Y stage are used to obtain the surface scanning UGW signal and the line scanning UGW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This work reported an inverse linear relationship between the ToF and the SOC and the authors also observed a shift towards lower ToF and higher amplitude of the ultrasonic guided waves as a function of the number of charge/discharge cycles during aging. Moreover, recent studies have correlated different characteristics of guided waves to the battery state [53–55] . It should be noted that guided waves often operate at lower frequencies than compression waves, and are well suited to prismatic and pouch form factors [56] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work reported an inverse linear relationship between the ToF and the SOC and the authors also observed a shift towards lower ToF and higher amplitude of the ultrasonic guided waves as a function of the number of charge/discharge cycles during aging. Moreover, recent studies have correlated different characteristics of guided waves to the battery state [53–55] . It should be noted that guided waves often operate at lower frequencies than compression waves, and are well suited to prismatic and pouch form factors [56] …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies have correlated different characteristics of guided waves to the battery state. [53][54][55] It should be noted that guided waves often operate at lower frequencies than compression waves, and are well suited to prismatic and pouch form factors. [56] Cylindrical LIBs are widely used in consumer electronics and have gained significant traction in the automotive industry, particularly with Tesla's announcement of the cylindrical 4680 format.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium-ion batteries have become an ideal candidate for electrochemical energy storage systems, which are widely used in portable electronic devices and electric vehicles due to their advantages of high energy density, long life cycles, and low environmental pollution. 1 Storing energy using lithium-ion batteries is one of the most efficient means of decarbonization and electrification because it could facilitate the use of renewable energy and reduce the energy dependence on fossil fuels (i.e. oil and gas).…”
mentioning
confidence: 99%
“…These traditional methods also require extra hardware and/or advanced algorithms, such as the Kalman filter, to acquire the measurements, and therefore, they are not very efficient in improving the efficiency of battery state estimation. 1,11 Current evaluation technologies for lithium-ion battery state are mainly focused on the SoC and the SoH because they indicate the battery's remaining capacity and aging level, respectively. 1,12 The SoC is expressed as a percentage (i.e., 0% for full discharge and 100% for full charge) and is a time-relative indication between the average lithium-ion concentration on the anode surface compared to the maximum concentration that could be stored in the electrode.…”
mentioning
confidence: 99%
See 1 more Smart Citation